Research on Recycled Concrete Aggregates at NUS - C.T Tam; K.C.G. Ong; A. Akbarnezhad; M.H. Zhang (Electronic Journal of Structural Engineering, 2013)
Sustainable concrete construction is critical to the economic development of infrastructures. The need and demand for infrastructure development is crucial to economic and social well-being of all nations. Of all the constituents in concrete coarse aggregate forms the biggest volume. As the reserve of aggregates is finite, the availability of suitable recycled concrete aggregate from demolition of concrete structures provides an alternate source to meet the increasing demand of new construction. Research on recycled concrete aggregate (RCA) at NUS was first conducted in the 1980’s. In recent years, further studies cover two main areas. The first is on the technique to improve the quality of recycled coarse concrete aggregate by means of microwave treatment. The other is to develop a modified acid treatment method to fully remove all attached materials from RCA coarse particles. This provides a more reliable basis for determination of the mortar content in RCA thus achieving a more precise relationship between properties of RCA and mortar content. Results on the relationship between 24-hour water absorption, bulk density and Los Angeles abrasion resistance of RCA and mortar content show a higher regression coefficient compared to others in published literature.